2001
DOI: 10.1080/01652176.2001.9695090
|View full text |Cite
|
Sign up to set email alerts
|

Haematology: Haematological and blood biochemical characteristics of Dutch warmblood foals managed under three different rearing conditions from birth to 5 months of age

Abstract: SUMMARY Reference values for haematological and blood biochemical variables may vary per breed and are influenced by age and, to a certain extent, by rearing conditions. To investigate the influence of age and rearing conditions, these variables were measured in Dutch Warmblood foals from birth to 5 months of age. The foals were divided into three groups with different exercise regimens:14 foals got boxrest with no exercise; 14 foals were kept in comparable boxes, but received daily exercise; and 15 foals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 7 publications
(16 reference statements)
4
14
0
6
Order By: Relevance
“…Essentially, it is known that antibodies produced by the foal's own immune system are detectable at 10-14 days of age (Knottenbelt et al, 2004). Moreover, the gradual increase of albumin, mainly produced in the liver, is probably related with the development of this organ (Koterba et al, 1990;Brommer et al, 2001). This confirms that animals' organ functions are in a development phase during the early neonatal period and a wide range of physiological values in different systems compensate for immaturity (Knottenbelt et al, 2004;Piccione et al, 2006Piccione et al, , 2009Zumbo et al, 2010).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Essentially, it is known that antibodies produced by the foal's own immune system are detectable at 10-14 days of age (Knottenbelt et al, 2004). Moreover, the gradual increase of albumin, mainly produced in the liver, is probably related with the development of this organ (Koterba et al, 1990;Brommer et al, 2001). This confirms that animals' organ functions are in a development phase during the early neonatal period and a wide range of physiological values in different systems compensate for immaturity (Knottenbelt et al, 2004;Piccione et al, 2006Piccione et al, , 2009Zumbo et al, 2010).…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, significantly higher levels of γ -globulins were found in days 12 and 30 with respect to day 1. According to other authors (Brommer et al, 2001;Axon and Palmer, 2008;Curcio and Nogueira, 2012;Piccione et al, 2013a, b), this finding demonstrated that serum total proteins and their fractions are involved in typical physiological and metabolic adjustments to early postnatal development and growth as adaptive response to various environmental factors after birth, including nutrition. The levels of these parameters are closely related to newborn ingestion of colostrum within the first hours of life (Axon and Palmer, 2008;Curcio and Nogueira, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Before accurate comparisons of plasma AVP concentrations can be made between healthy and ill foals, investigation of age‐related changes in AVP concentrations in healthy foals is a prudent initial objective because of the dynamic and rapidly changing nature of the growing foal. Indeed, various clinicopathologic parameters have demonstrated notable differences as the foal ages 9–12 . The purpose of the study presented here was to determine if age‐related differences in plasma AVP concentrations occur in healthy foals from birth to 3 months of age.…”
mentioning
confidence: 99%
“…Some aspects of foals' physiology during postnatal period including endocrine [4], metabolism [11], biochemical [11,12], and hematological [12,13] profiles were investigated. Few studies dealt with modification of clotting profile in healthy newborn foals [6,10,14], whereas, to our knowledge, no research on platelet functional activity in equine species are reported during the early postpartum period.…”
Section: Introductionmentioning
confidence: 99%